'Going digital' - Lessons for future coastal community engagement and climate change adaptation. (1st July 2021) - McKinley, E.; Crowe, P.R.; Stori, F.; Ballinger, R.; Brew, T.C.; Blacklaw-Jones, L.; Cameron-Smith, A.; Crowley, S.; Cocco, C.; O'Mahony, C.; McNally, B.; Power, P.; et al.
Abstract: Recent decades have witnessed a steady increase in efforts from a range of actors to facilitate and support meaningful and effective engagement with coastal communities and stakeholders. Indeed, this move towards improved participatory approaches are increasingly framed as being integral to successful and sustainable management of coastal resources and spaces, including in the context of climate adaptation The effectiveness of the processes, structures and frameworks underpinning coastal community engagement has always been subject to external and internal drivers; however, the global threat posed by COVID-19 presented, and continues to present, an unexpected shift in approach, and the need for rapid adaptation by those of us working within these spheres. Using the Coastal Communities Adapting Together (CCAT) project as a case study, we explore how engagement with coastal communities and stakeholders in the project areas of Fingal, Ireland, and Pembrokeshire, Wales, has been impacted and forced to adapt as a result of COVID-19. Through a qualitative data collection process, we explore how project teams across different scales have rapidly adapted their models of community and stakeholder engagement, identify successes and failures, and explore challenges that have been faced. Finally, we consider if the legacy of COVID-19 has provided an opportunity for coastal community engagement approaches being used across the globe to become more diverse, adapting to new technologies and increasing accessibility and effectiveness. Insights identified as fundamental to successful adaptation and enhancing resilience include: a rapid response to change, adoption of a diversity of techniques, broadened participation and supported social learning and knowledge exchange. Highlights: Explores impacts and adaptation in coastal community engagement as a result of COVID-19. Using four CCAT activities, a range of techniques, challenges and opportunities are discussed. 'Going digital' has a range of benefits but should not be viewed as a 'one size fits all' solution to engagement. Adaptation and resilience require rapid response, use of diverse techniques, broad participation and supported learning.